Tuberculosis‐associated chylothorax revealing an enlarged lymphatic duct due to tuberculosis lymphadenitis - Honda, Kojiro (Respirol Case Rep, 2020)
A 77‐year‐old woman presented to our hospital with complaints of persistent cough and low‐grade fever for two months. On radiological analysis, she had moderate right‐sided pleural effusion with right hilar and subcarinal lymphadenopathies. Thoracentesis showed chylothorax of unknown cause. Bronchoscopy revealed a non‐specific inflammatory process. However, thoracoscopic surgery demonstrated a curiously enlarged lymphatic duct with its proximal portion compressed by subcarinal lymphadenopathies, pathologically diagnosed as granulomatous lymphadenitis. Hence, tuberculous lymphadenitis was proven to be the cause of chylothorax. Interestingly, cauterization of the lymphatic duct decreased the total amount of right‐sided pleural effusion along with a change in colour from milky yellow to red. These were in favour of tuberculosis (TB)‐associated chylothorax with the advent of the TB pleuritis. All symptoms and pleural effusion disappeared after the initiation of anti‐tuberculous drugs. The present case showed definite evidence of TB‐associated chylothorax development mechanism via compression of the lymphatic duct by mediastinal lymphadenopathies.